Investigation of mesh dependency issues in the simulation of crack propagation in quasi‐brittle materials by using a diffuse interface modeling approach. Issue 3 (23rd December 2021) - Pascuzzo, Arturo; Greco, Fabrizio; Leonetti, Lorenzo; Lonetti, Paolo; Pranno, Andrea; Ronchei, Camilla
Abstract: This work proposes an efficient cohesive finite element modeling approach based on a diffuse interelement interface strategy to reproduce the fracture behavior of quasi‐brittle materials under general loading conditions. The proposed model involves zero‐thickness interface elements, whose strength and toughness properties are spatially randomized, thus avoiding the well‐known nonuniqueness issues that can affect the stability of the associated numerical computations, which potentially lead to physically meaningless predictions of the fracture behavior. The reliability of the proposed refined fracture approach is assessed by performing several numerical simulations of the direct tensile test on various quasi‐brittle specimens. Results show that a proper calibration of the cohesive properties of the diffuse embedded interfaces is fundamental to ensure the desired numerical accuracy and stability properties. Besides, comparisons with experimental and numerical data found in the literature are used to fully validate the proposed approach.